Nurse-physician collaboration and associations with perceived autonomy in Cypriot critical care nurses - Georgiou, Evanthia; Papathanassoglou, Elizabeth; Pavlakis, Andreas (My University, 2017)
Background and aims: Increased nurse-physician collaboration is a factor in improved patient outcomes. Limited autonomy of nurses has been proposed as a barrier to collaboration. This study aims to explore nurse-physician collaboration and potential associations with nurses' autonomy and pertinent nurses' characteristics in adult intensive care units (ICUs) in Cyprus. Design and Methods: Descriptive correlational study with sampling of the entire adult ICU nurses' population in Cyprus (five ICUs in four public hospitals, n = 163, response rate 88·58%). Nurse-physician collaboration was assessed by the Collaboration and Satisfaction About Care Decisions Scale (CSACD), and autonomy by the Varjus et al. scale. Results: The average CSACD score was 36·36 ± 13·30 (range: 7–70), implying low levels of collaboration and satisfaction with care decisions. Male participants reported significantly lower CSACD scores (t = 2·056, p = 0·04). CSACD correlated positively with years of ICU nursing experience (r = 0·332, p < 0·0001) and professional satisfaction (r = 0·455, p < 0·0001). The mean autonomy score was 76·15 ± 16·84 (range: 18–108). Higher degree of perceived collaboration (CSACD scores) associated with higher autonomy scores (r = 0·508, p <0·0001). Conclusions: Our findings imply low levels of nurse-physician collaboration and satisfaction with care decisions and moderate levels of autonomy in ICU nurses in Cyprus. Relevance to clinical practice: The results provide insight into the association between nurse-physician collaboration and nurses' autonomy and the correlating factors.
Keywords: Autonomy; Clinical decision-making; Collaboration; Critical care; Power disparities; Professional satisfaction